The Christmas truce : myth, memory, and the First World War - Crocker, Terri Blom (University Press of Kentucky, 2015)
The 1914 Christmas truce, when enemy soldiers met, fraternized, and even played football in No Man's Land during the first year of the First World War, is commonly perceived as a manifestation of the anger that soldiers felt toward the meaningless war that they had been tricked into fighting. Contemporaneous sources, however, show that the truce was not an act of defiance; rather, it arose from the professionalism of the soldiers involved, the conditions of static trench warfare, foul weather on the Western Front, the absence of major battles, and memories of traditional celebrations of Christmas. The truce, in short, was caused by rain, mud, curiosity, lack of personal animosity toward the enemy, and homesickness, rather than by frustration and rebellion.